Gut-dependent inflammation and alterations of the intestinal microbiota in individuals with perinatal HIV exposure and different HIV serostatus. (15th November 2022) - Tincati, Camilla; Ficara, Monica; Ferrari, Francesca; Augello, Matteo; Dotta, Laura; Tagliabue, Claudia; Diana, Alfredo; Camelli, Vittoria; Iughetti, Lorenzo; Badolato, Raffaele; Cellini, Monica; Marchetti, Giulia
Abstract : Objective: HIV-exposed infected (HEI) and uninfected (HEU) children represent the two possible outcomes of maternal HIV infection. Modifications of the intestinal microbiome have been linked to clinical vulnerability in both settings, yet whether HEI and HEU differ in terms of gut impairment and peripheral inflammation/activation is unknown. Design: We performed a cross-sectional, pilot study on fecal and plasma microbiome as well as plasma markers of gut damage, microbial translocation, inflammation and immune activation in HIV-infected and uninfected children born from an HIV-infected mother. Methods: Fecal and plasma microbiome were determined by means of 16S rDNA amplification with subsequent qPCR quantification. Plasma markers were quantified via ELISA. Results: Forty-seven HEI and 33 HEU children were consecutively enrolled. The two groups displayed differences in fecal beta-diversity and relative abundance, yet similar microbiome profiles in plasma as well as comparable gut damage and microbial translocation. In contrast, monocyte activation (sCD14) and systemic inflammation (IL-6) were significantly higher in HEI than HEU. Conclusion: In the setting of perinatal HIV infection, enduring immune activation and inflammation do not appear to be linked to alterations within the gut. Given that markers of activation and inflammation are independent predictors of HIV disease progression, future studies are needed to understand the underlying mechanisms of such processes and elaborate adjuvant therapies to reduce the clinical risk in individuals with perinatal HIV infection.